Going Offshore: Investments in German Wind Energy under Uncertainty - Yu-Fu Chen; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2015)
Employing a continuous-time real options modeling framework, this paper scrutinizes the incentives to invest in German offshore wind farms. The focus of the analysis is the mode of action of the German feed-in tariff system for offshore wind energy deployment. The numerical results reveal that the long term subsidies in Germany set prices that provide higher returns than needed to secure investment, even when taking the uncertainties involved into account. The results obtained can be used by policy-makers to design comprehensive and efficient offshore wind energy support measures.
Keywords: C61; D92; E22; H23; O33; 330; real options; offshore wind energy; feed-in tariff; tender bidding; Germany